Genetic diversity and population structure of bermudagrass (Cynodon spp.) revealed by genotyping-by-sequencing - Singh, Lovepreet; Wu, Yanqi; McCurdy, James D.; Stewart, Barry R.; Warburton, Marilyn L.; Baldwin, Brian S.; Dong, Hongxu (Frontiers in Plant Science, 2023)
Bermudagrass (Cynodon spp.) breeding and cultivar development is hampered by limited information regarding its genetic and phenotypic diversity. To explore diversity in bermudagrass, a total of 206 Cynodon accessions consisting of 193 common bermudagrass (C. dactylon var. dactylon) and 13 African bermudagrass (C. transvaalensis) accessions of worldwide origin were assembled for genetic characterization. Genotyping-by-sequencing (GBS) was employed for genetic marker development. With a minor allele frequency of 0.05 and a minimum call rate of 0.5, a total of 37,496 raw single nucleotide polymorphisms (SNPs) were called de novo and were used in the genetic diversity characterization. Population structure analysis using ADMIXTURE revealed four subpopulations in this germplasm panel, which was consistent with principal component analysis (PCA) and phylogenetic analysis results. The first three principal components explained 15.6 %, 10.1 %, and 3.8 % of the variance in the germplasm panel, respectively. The first subpopulation consisted of C. dactylon accessions from various continents; the second subpopulation was comprised mainly of C. transvaalensis accessions; the third subpopulation contained C. dactylon accessions primarily of African origin; and the fourth subpopulation represented C. dactylon accessions obtained from the Oklahoma State University bermudagrass breeding program. Genetic diversity parameters including Nei’s genetic distance, inbreeding coefficient, and Fst statistic revealed substantial genetic variation in the Cynodon accessions, demonstrating the potential of this germplasm panel for further genetic studies and cultivar development in breeding programs.